Green Enterprises as a Catalyst for Strengthening Community Capacity in Local Reconstruction Efforts in Western Nepal - Chongbang , Nirmal; Rawal, Dipina Sharma; Iskamto, Dedi (ADPEBI International Journal of Business and Social Science, 2025)
This study examines how rational contributing on green reconstruction support from establishment of 26 green enterprises in these regions, supported by local, provincial, and federal governments with development partners, aimed at generating local employment, fostering a circular economy, and reducing carbon emissions. The use of CSEBs provides a sustainable alternative to traditional building materials, with an estimated reduction of 15 million tons of CO2 emissions compared to conventional red-brick construction. These enterprises, empowered by local governments and external stakeholders, promote eco-friendly and thermal-efficient construction practices, contributing to both environmental sustainability and economic resilience. Through a qualitative approach, this research employs quantitative calculation, qualitative data collection, multiple reality as ontology, interpretivism as epistemology, and inductive methodology to explore how these green enterprises contribute to climate-resilient infrastructure and sustainable development in western rural Nepal. The study underscores the potential of green technology-driven local enterprise solutions in post-disaster reconstruction, advocating for sustainable, low-carbon building practices as a model for future disaster recovery efforts.